Media Sosial sebagai Faktor Perceraian di Wilayah Hukum Pengadilan Tinggi Agama Padang - Desminar Desminar; Asasriwarni Asasriwarni; Ikhwan Ikhwan (Jurnal Kajian dan Pengembangan Umat, 2022)
To realize the purpose of marriage, there are many challenges and trials experienced by husband and wife due to the uncontrolled use of sosial media which leads to divorce. Divorce occurs due to several factors including the influence of sosial media. The development of sosial media brings many benefits to society, but if it is not wise in its use, it is very detrimental to its users. This type of research is field research with a qualitative approach. Data were collected by interview and study of documents regarding divorce cases caused by the influence of sosial media in the jurisdiction of the Padang High Court of Religion. Furthermore, the data were analyzed descriptively with reduction, display and verification techniques. The results of the first study are that the legal basis used by the Panel of Judges in resolving this case is Government Regulation no. 9 of 1975 Article 19 hruf (c) in conjunction with Islamic Law Compilation Article 116 haruf (g and h) by considering the arguments for benefit to avoid negative things that will arise for the plaintiff and the defendant. Furthermore, the results of the second study are the forms of sosial media that cause divorce based on the analysis of the six decisions, namely: first, establishing quite intense communication via telephone with one of the defendant's ex-lover. The two defendants had an affair on Facebook, the three defendants often cheated on Facebook with other women. The four defendants often called other women. The five defendants often communicated with other men on their cellphones. The six applicants found another cellphone number in the respondent's cellphone which contained repeated short messages.